Medium and long run economic assimilation of Venezuelan migrants to Peru - Javier Torres; Javier Beverinotti; Gustavo Canavire-Bacarreza (Inter-American Development Bank (IDB), 2024)
In a span of six years, the proportion of Venezuelans in Perú has surged nearly fourfold, rising from virtually zero to over 4% of the population. This study delves into the dynamics of medium- and long-term labor market integration in Perú, combining data from the Venezuelan Population Residing in Perú Survey and the Peruvian National Household Survey. Our findings reveal that Venezuelan workers experience low returns on foreign postsecondary education and there is minimal relation between foreign work experience and monthly income. Importantly, these outcomes remain consistent irrespective of the time spent in the host country, indicating a gradual economic assimilation process. Lastly, our estimation demonstrates that if Venezuelans' human capital yielded returns equivalent to Peruvian human capital, the average income of Venezuelans would witness a substantial increase of 20%.
Keywords: J15; J24; J31; J70; 330; Immigration; Economic Assimilation; Wage Discount